Strategies for discovering new antibiotics - Cox, Jonathan (Henry Stewart Talks, 2021)
The history of antibiotics, Antibiotic resistance, Antibiotic development, The need for new antibiotics, The antibiotic golden age, Target to drug and drug to target strategies, Challenges in antibiotic development, The future of antibiotic discovery